Effect of the guided inquiry model on students’ creative thinking skills - Yuniarti Mellia Triana; Sri Untari; Didik Sukriono (Inovasi Kurikulum, 2026)
Creative thinking has become a fundamental competency for 21st-century learners and needs to be cultivated through meaningful classroom practices. This study analyzes the impact of the guided inquiry learning model, applied through a case study, on the creative thinking abilities of eighth-grade students at SMP Negeri 1 Pakis. The research employed a quasi-experimental design with a non-equivalent control group, with class VIII D (34 students) as the experimental group and class VIII B (34 students) as the control group. Data were obtained from essay tests on creative thinking administered before and after learning, complemented by observation sheets and documentation. The data analysis included descriptive statistics, normality and homogeneity tests, paired-samples t-tests, and independent-samples t-tests. The findings revealed that although both groups started with comparable initial abilities, students in the experimental group demonstrated significantly greater improvement after treatment, especially in fluency, flexibility, originality, and elaboration. These results suggest that guided inquiry learning is effective in enhancing creative thinking and can be implemented as an alternative strategy to promote higher-order thinking in Civics Education.   Abstrak Kemampuan berpikir kreatif merupakan kompetensi penting abad ke-21 yang perlu ditumbuhkan melalui pembelajaran yang bermakna di sekolah. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran inkuiri terbimbing dengan pendekatan studi kasus terhadap kemampuan berpikir kreatif murid kelas VIII SMP Negeri 1 Pakis. Penelitian ini menggunakan metode kuasi-eksperimen dengan desain non-equivalent control group, melibatkan kelas VIII D (34 murid) sebagai kelompok eksperimen dan kelas VIII B (34 murid) sebagai kelompok kontrol. Data penelitian diperoleh melalui tes esai berpikir kreatif yang diberikan sebelum dan setelah pembelajaran, serta diperkuat dengan lembar observasi dan dokumentasi. Analisis data dilakukan menggunakan statistik deskriptif, uji normalitas, uji homogenitas, uji t berpasangan, dan uji t independen. Hasil penelitian menunjukkan bahwa meskipun kedua kelompok memiliki kemampuan awal yang relatif seimbang, peningkatan yang lebih signifikan ditunjukkan oleh kelompok eksperimen setelah perlakuan, terutama pada aspek kelancaran, keluwesan, orisinalitas, dan elaborasi. Temuan ini membuktikan bahwa model pembelajaran inkuiri terbimbing efektif dalam mengembangkan kemampuan berpikir kreatif dan dapat dijadikan strategi alternatif untuk menumbuhkan keterampilan berpikir tingkat tinggi dalam pembelajaran PPKn. Kata Kunci: berpikir kreatif; inkuiri terbimbing; model pembelajaran; Pendidikan Pancasila dan Kewarganegaraan